Tacrolimus in the prevention of adverse pregnancy outcomes and diabetes-associated embryopathies in obese and diabetic mice. Issue 1 (December 2017) - Albaghdadi, Ahmad; Hewitt, Melanie; Putos, Samantha; Wells, Michael; Ozolinš, Terence; Kan, Frederick
Abstract Background T2DM is a high-risk pregnancy with adverse fetal and maternal outcomes including repeated miscarriages and fetal malformations. Despite the established association between placental insufficiency and poor maternal Th1-adaptability to the development of pregnancy complications in T2DM, there have been no established data to assess benefits of pre-pregnancy immunosuppression relative to gestational outcomes in T2DM. We hypothesized that pre-pregnancy macrolide immune suppression can re-establish normal placental development and uterine vascular adaptation in a mouse model of obesity-associated T2DM. Methods Fetal live birth rate, postnatal variability, mid-gestational uterine and umbilical flow dynamics and certain morphological features of spiral artery modification were examined in the New Zealand Obese (NONcNZO10/Ltj) female mice (n = 56) weaned to ages of 32 weeks on a 60% calories/g high-fat diet (also referred to as HFD-dNONcNZO), and which received either tacrolimus (0.1 mg/kg s.c. q2d), its vehicle (castor oil and ethanol) or metformin (in drinking water 200 mg/dL p.o. ad libitum). HFD-BALBc-Rag2/IL2-gc female mice (n = 24) were used as HFD-immunodeficient controls. Results Treatment of the HFD-dNONcNZO female mice with tacrolimus improved live birth rates and postnatal viability scores (p < 0.01), normalized OGTT (p < 0.001), inhibited fetal malformation rates, restored morphology of spiral arterial modification; and improved uterine arterial and umbilical blood flow (p < 0.01). Placental production of TNFαand IL16 in the tacrolimus-treated HFD-dNONcNZO dams were restored to non-diabetic levels and the treatment resulted in the inhibition of aberrant monocyte/macrophage activation during pregnancy in the HFD-dNONcNZO dams. Conclusions Our present data suggest a casual association between chronic maternal overnutrition and aberrancy in the maternal Th1-immune maladaptation to pregnancy and defective spiral artery modification, placental insufficiency and adverse fetal outcomes in the T2DM subjects. Further safety studies into the use of tacrolimus in the pre-pregnancy glycemic control may be beneficial.